Effect of varying levels and sources of dietary fat on growth performance and nutrient gigestibility in rabbits - M. L., Egbo; T. A., Adegbola; E. O., Oyawoye; M. M., Abu Bakar (Universiti Putra Malaysia Press, 2004)
The effects of dietary fat sources and levels on growth performance and nutrient digestibility were investigated in cross-breed Lopx New Zealand rabbits. Fifty weaned rabbits were randomly allotted to five dietary treatments consisting of a control (no fat) and four others with fat, either from plant (groundnut oil) or animal (butter) sources, each at two levels (3% and 6%) of inclusion. There were ten rabbits per diet. Rabbits on 6% animal fat-based diet recorded the highest (P<O.Ol) better in rabbits on 6% animal diet. Organic matter intake (OMI) was observed to be similar between rabbits fed control and 3% animal fat diets. However, the 6% butter fat diet recorded the lowest. Crude protein digestibility (CPD) was similar in rabbit fed 3% and 6% level of animal fat which were the highest while 6% level of plant fat diet had the lowest CPD. These findings show that the inclusion of animal fat at 6% level improved the weight gain and efficiency of feed utilization in rabbits.